2013
DOI: 10.5152/eajm.2013.37
|View full text |Cite
|
Sign up to set email alerts
|

Is a Drain Required after Laparoscopic Cholecystectomy?

Abstract: Objective: Whether drains should be routinely used after laparoscopic cholecystectomy is still debated. We aimed to retrospectively evaluate the benefits of drain use after laparoscopic cholecystectomy for non-acute and non-inflamed gallbladders. Materials and Methods:Two hundred and fifty patients (mean age, 47±13.8 years; 200 females and 50 males) who underwent laparoscopic cholecystectomy for cholestasis were included in the study. The medical files of the patients were examined retrospectively to obtain da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
2
3
0
1
Order By: Relevance
“…However, controversies have surrounded this practice. 8,9 Mean hospital stay of patients in the group without drainage was less in our study, which is similar to the studies conducted by Gurusamy et al 10 and Satinsky et al 11 Patients complain of postoperative shoulder pain, nausea and vomiting, due to use of a shortterm drain postoperatively based on the theory that high-pressure CO2 insufflation during the operation and the accumulation of gas in the right subphrenic area leads to these complaints. [3][4][5][6] The results showed no significant differences in postoperative complications in the two groups (with and without drain) i.e., wound infections, mortality, respiratory infection and/or nausea.…”
Section: Discussionsupporting
confidence: 90%
“…However, controversies have surrounded this practice. 8,9 Mean hospital stay of patients in the group without drainage was less in our study, which is similar to the studies conducted by Gurusamy et al 10 and Satinsky et al 11 Patients complain of postoperative shoulder pain, nausea and vomiting, due to use of a shortterm drain postoperatively based on the theory that high-pressure CO2 insufflation during the operation and the accumulation of gas in the right subphrenic area leads to these complaints. [3][4][5][6] The results showed no significant differences in postoperative complications in the two groups (with and without drain) i.e., wound infections, mortality, respiratory infection and/or nausea.…”
Section: Discussionsupporting
confidence: 90%
“…Post-operative subhepatic collection: In this study, we found that overall 66.67% of cases were female & 33.33% cases were male. Similar sex preponderance in favour of females was observed by Dumlu et al [9] in their study with 5:1 (F: M ratio). The study done by Aman Nagpal et al [7] also showed the male female ratio as 1:3.…”
Section: Discussionsupporting
confidence: 89%
“…Statistically and from previous studies, there is no correlation between fluid collection post LC or by the conventional method [ 22 - 23 ]. Limited data are available on the outcome of abdominal collection in a port site infection after dry mopping versus saline irrigation post biliary spillage.…”
Section: Discussionmentioning
confidence: 95%